Organisasi Integrated Curriculum dalam Implementasi Pembelajaran Berbasis Life Skill di Sekolah Dasar - M Choirul Muzaini; Rizky Rahayu; Vega Bintang Rizky; Muhammad Najib; Muhamad Supriadi; Andi Prastowo (Universitas Pendidikan Mandalika, 2023)
The study aims to describe the integrated curriculum organizational management in implementing life skill-based learning in elementary schools. This research method was descriptive, using the type of field research. The informants in this study were the principal and deputy principal of the curriculum section at SDN Samirono. Data collection techniques used observation, interviews, and documentation. While the data analysis techniques in this study used data reduction, data presentation, and conclusions, as well as data validity assurance techniques using source triangulation. This study found that the planning, organizing, implementing, and evaluating the integrated curriculum organization in implementing learning to foster students' life skills at SDN Samirono had been carried out well. Management was carried out based on standards that had been decided. There was an agenda for monitoring carried out internally and externally and measuring achieving objectives in implementing the integrated curriculum organization.